2019
DOI: 10.18632/aging.101820
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical effects of Emblica officinalis in age-related macular degeneration

Abstract: Emblica officinalis Gaetrn ( i.e., Phyllanthus emblica/ Indian gooseberry/ Amla) (EO) has been used extensively as a nutraceutical in several diseases since it is known to boost immunity and offers numerous health benefits such as antioxidant, anti-inflammatory, and anti-aging effects. The goal of our study was to test the hypothesis that EO will rescue human AMD RPE transmitochondrial cells from mitochondria-induced cellular damage. AMD RPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…All AMD patients used in this study have been clinically characterized, and genetic and clinical information of all patients is available as partly mentioned in Table 1. Morphological and functional evaluation of these AMD RPE transmitochondrial cell lines in our previous studies revealed significant mitochondrial and cellular damage as evidenced by apoptotic cell death, higher oxidative stress, low antioxidant content, lower numbers of mitochondria, and higher mtDNA fragmentation in AMD RPE cells [9][10][11][12][13]. Therefore, AMD RPE transmitochondrial cell lines serve as a good in vitro model to test the effects of resveratrol as a potential over-the-counter candidate for AMD therapy.…”
Section: Discussionmentioning
confidence: 94%
“…All AMD patients used in this study have been clinically characterized, and genetic and clinical information of all patients is available as partly mentioned in Table 1. Morphological and functional evaluation of these AMD RPE transmitochondrial cell lines in our previous studies revealed significant mitochondrial and cellular damage as evidenced by apoptotic cell death, higher oxidative stress, low antioxidant content, lower numbers of mitochondria, and higher mtDNA fragmentation in AMD RPE cells [9][10][11][12][13]. Therefore, AMD RPE transmitochondrial cell lines serve as a good in vitro model to test the effects of resveratrol as a potential over-the-counter candidate for AMD therapy.…”
Section: Discussionmentioning
confidence: 94%
“…IncuCyte live-cell imaging was performed as described previously [69]. The IncuCyte NucLight Rapid Red Reagent is a cell permeable DNA stain that specifically stains nuclei in live cells and enables real-time quantification of cell proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…Biological source: Emblica officinalis Immunity boosting mechanism: It is a rich source of antioxidants, including polyphenols, which confer its free radical scavenging potential (56). 1349 13) Guduchi: Biological source: Tinospora cordifolia Immunity boosting mechanism: It increases the concentration of cytokines.…”
Section: ) Amlamentioning
confidence: 99%